2022
DOI: 10.1044/2022_ajslp-21-00312
|View full text |Cite
|
Sign up to set email alerts
|

Intraword Variability in Children With Auditory Brainstem Implants: A Longitudinal Comparison With Children With Cochlear Implants

Abstract: Purpose: Intraword variability designates the phenomenon that a particular target word is produced variably by a child at one point in the child's development. In this study, the amount of intraword variability is studied longitudinally in children with auditory brainstem implants (ABIs). Auditory brainstem implantation is a relative recent technique in pediatric hearing restoration. Therefore, little is known about the phonological development of these children's speech. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The ultimate objective is to deliver tactile input similar to that of a human limb. Giacomo Valle et al examined the possibility of constructing natural tactile experiences via biomimetic hybrid sensory encodings [27]. The approach converts input into electrical stimulations and transfers them to peripheral intraneural regions in order to generate tactile sensations [27].…”
Section: Tactile Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The ultimate objective is to deliver tactile input similar to that of a human limb. Giacomo Valle et al examined the possibility of constructing natural tactile experiences via biomimetic hybrid sensory encodings [27]. The approach converts input into electrical stimulations and transfers them to peripheral intraneural regions in order to generate tactile sensations [27].…”
Section: Tactile Rehabilitationmentioning
confidence: 99%
“…Giacomo Valle et al examined the possibility of constructing natural tactile experiences via biomimetic hybrid sensory encodings [27]. The approach converts input into electrical stimulations and transfers them to peripheral intraneural regions in order to generate tactile sensations [27]. Not only that, but a number of research groups have found that artificial tactile considerably improves user performance and ability [27][28][29].…”
Section: Tactile Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation